2007
DOI: 10.2319/070706-281
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Cervical Headgear vs Rapid Maxillary Expander and Facemask for Orthopedic Treatment of Class III Malocclusion

Abstract: Objective:To compare the effectiveness of the rapid maxillary expander and facemask (RME/ FM) and mandibular cervical headgear (MCH) protocols when followed by fixed appliances and evaluated at a postpubertal observation in patients with dentoskeletal Class III malocclusion. Materials and Methods: The sample treated with the RME/FM followed by fixed appliances included 32 patients (12 boys and 20 girls). The sample treated with the MCH followed by fixed appliances included 26 patients (eight boys and 18 girls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
2
17
0
7
Order By: Relevance
“…A magnitude média determinada no presente trabalho foi de 447,8g, estando condizente com a maioria das recomendações dos demais estudos 2,3,5,6,9,10,19,21,23,32,33,35,42 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A magnitude média determinada no presente trabalho foi de 447,8g, estando condizente com a maioria das recomendações dos demais estudos 2,3,5,6,9,10,19,21,23,32,33,35,42 .…”
Section: Discussionunclassified
“…MacDonald, Kapust e Turley 24 utilizaram uma força entre 200g e 450g (média 325g) e diversos autores afirmaram utilizar uma força entre 300g e 500g (média 400g) 5,6,10,41,43 , próxima da empregada nos estudos que usaram 500g de força 2,19,23,32,33 .…”
Section: Magnitude De 300g a 500gunclassified
See 2 more Smart Citations
“…Wolfe et al reported that, compared with a Class I control group, patients with Class III malocclusion display hyperdivergent jaws and increased inferior facial height (Wolfe, Araujo, Behrents, & Buschang, ). Treatment has been aimed at maxillary advancement and/or control of jaw growth, and several devices have been designed for this purpose such as protraction face masks (FMs), chincups, mandibular cervical hedgear, and functional orthopedic appliances (Baccetti, Rey, Angel, Oberti, & McNamara, ; Baccetti, Rey, Oberti, Stahl, & McNamara, ; Baik, Jee, Lee, & Oh, ; Rey, Angel, Oberti, & Baccetti, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%